Cross-border trade in services - Martina Lawless (The Economic and Social Research Institute (ESRI), 2021)
This report examines the extent of cross-border trade in services on the island of Ireland and the characteristics of the firms participating in this trade. Although services make up a substantial and growing portion of economic activities in both Ireland and Northern Ireland, data limitations have resulted in less focus being placed on services flows when compared to goods trade. Given the strong links established between exporting and economic growth, an understanding of the structure and composition of trade is necessary to provide evidence for a supportive policy environment for firms and to enhance further all Island economic links. A key contribution of the report is a stocktake of the various data sources available on cross-border services trade. This draws attention to some of the differences in data collected in Ireland and Northern Ireland and where there are data gaps that could be addressed in the future. Given the differences in data sources, some caveats are made throughout the report on direct comparisons and a recommendation is made for the benefits of collection of more systematically comparable data on an all-island basis.
Keywords: 330